ANALISIS YURIDIS PERLINDUNGAN HUKUM BAGI ANAK SEBAGAI KURIR NARKOTIKA DITINJAU BERDASARKAN SISTEM PERADILAN PIDANA ANAK DAN SISTEM PERLINDUNGAN ANAK DI INDONESIA - Muhammad Abid Alhafiz; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
To trick the authorities, it is not uncommon for narcotics dealers to use minors to be couriers of these illegal drugs. Lack of knowledge of narcotics, and the inability to resist and fight against makes minors become targets of narcotics dealers to distribute narcotics widely and in disguise. This problem is certainly a very serious problem, because it can plunge minors into the illicit narcotics business.The type of research used in writing this law is normative legal research that focuses on the level of legal synchronization. This legal synchronization analyzes the extent to which a particular law or legislation is compatible vertically and horizontally which does not cause different interpretations from one another. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the research results are First, the regulation of legal protection for children as drug couriers based on the criminal justice system for children and the child protection system in Indonesia which is regulated in the provision of diversion or the severity of which prohibitions on diversion and the severity of the criminal offense released by the panel court. judges because they have not seen the diversion and imposition of crimes from a child protection perspective The judge still sees the perpetrator's child not as a victim, even though in the juvenile court system, children should not be justified as perpetrators. Second, the weaknesses of legal protection arrangements for children as drug couriers are reviewed based on the child criminal justice system and the child protection system in Indonesia, one of which is that Article 114 of Law Number 35 of 2009 concerning Narcotics does not limit age in court, both adults and children in court. underage, so that children as narcotics couriers can still be convicted even though the children's abilities are still limited and not as perfect as adults.Keywords: Narcotics, Legal Protection, Children, Couriers